Inclusive W and Z production in the forward region at root s=7TeV - Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2012)
Measurements of inclusive W and Z boson production cross-sections in pp collisions at √ s = 7TeV using final states containing muons are presented. The data sample corresponds to an integrated luminosity of 37 pb -1 collected with the LHCb detector. The W and Z bosons are reconstructed from muons with a transverse momentum above 20 GeV/c and pseudorapidity between 2:0 and 4:5, and, in the case of the Z cross-section, a dimuon invariant mass between 60 and 120 GeV/c 2. The cross-sections are measured to be 831±9±27±29 pb for W +, 656±8±19±23 for W - and 76:7±1:7±3: 3±2:7 pb for Z, where the first uncertainty is statistical, the second is systematic and the third is due to the luminosity. Differential cross-sections, W and Z cross-section ratios and the lepton charge asymmetry are also measured in the same kinematic region. The ratios are determined to be σW+ →μ+ν/ σW- →μ-ν = 1:27±0:02±0:01 and ( σW+ →μ+ν+ σW- →μ-ν) /σZ→μμ = 19:4±0:5± 0:9. The results are in general agreement with theoretical predictions, performed at nextto- next-to-leading order in QCD using recently calculated parton distribution functions. Copyright CERN.